The Role Of Human Capital Activation In Achieving The Outstanding Performance Of Tishreen University - مرهج, ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aimed at determining the role of Human Capital Activation in achieving the outstanding performance of Tishreen University. The researcher relied on the methodological approach as a general approach to research, followed the methodology of the survey, and a set of methods, including relying on secondary and primary data through a questionnaire that was organized by the researcher's knowledge of published literature. He distributed the questionnaire to 331 members of the faculty of Tishreen University, 259 of which were recovered, and 5 were not valid for analysis, and then used the appropriate statistical tests, such as simple regression, and rely on a programme SPSS is applying to be a tool for analysis of Data available. The main conclusion was a moral role, and Strong correlation between Human Capital Activation and the outstanding performance, and that the university's supervision of implementing internal development programs and providing them with an environment conducive to creativity and innovation was not required. Some suggestions and recommendations were presented to improve the relationship, which is the most important: the need to work to improve the efficiency of the educational process, focus on the customer and operations, and activate the role of leadership and governance.